Approaches to learning Arabic in KMA 183/2019 - Ali Maksum; Nana Jumhana; Umihani Umihani (EL-IBTIKAR: Jurnal Pendidikan Bahasa Arab, 2025)
ABSTRAKA correct and comprehensive understanding of the approach and theoretical basis of a curriculum will have implications for the implementation of learning carried out by teachers in the classroom. Based on this, the author conducted a study aimed at examining the approach and theoretical basis of Arabic language learning in the 2019 KMA 183 Arabic Language curriculum. This study uses a qualitative approach with a content analysis method. Data collection was carried out through documentation studies and also interviews and observations. The results of the study indicate that the Arabic language learning approach contained in the formulation of KI and KD leads to a genre-based language learning approach (text-based learning) which is a development of the communicative approach and comes from functional linguistics theory. However, the formulation of Core Competencies and Basic Competencies in the revised curriculum is not fully in accordance with the text-based language learning approach. For policy makers of the new KMA 183 curriculum, it is necessary to create an academic manuscript related to the new curriculum.Keywords: curriculum, Arabic, text-based approach, core competencies, basic competencies